ANALISIS YURIDIS TERHADAP PENGONSUMSIAN SATWA LIAR YANG TIDAK DILINDUNGI BAGI KESEHATAN MASYARAKAT INDONESIA - Bahiya, Balqis Ghaida; Ronaboyd, Irfa (Universitas Negeri Surabaya, 2022)
The writing of this study aims to analyze the Consumption of Unprotected Wildlife for Indonesian Public Health, this research is a normative legal research, which is carried out by means of a Statutory Approach, a Legislative Approach, and a Conceptual Approach. This approach departs from the views and doctrines that developed in legal science related to Juridical Analysis of the Consumption of Wildlife That Are Not Protected for Indonesian Public Health. There are incomplete norms that make these laws and regulations do not have a strong foundation to solve problems related to the consumption of unprotected wildlife. In the case of zoonotic diseases, there is no specific regulation regarding the consumption of wildlife, there are incomplete norms related to the case where if the consumption of wildlife continues, it is likely that the Indonesian state will experience another outbreak event in the future. In order to create regulations to deal with the spread of the plague through wildlife, it is necessary to have regulations that regulate matters related to food or consumption of wildlife that are susceptible to spreading the virus to humans so that it will become a dangerous outbreak. Keywords: Wildlife consumption, Zoonotic Diseases, Food Health, Food, plague